Progress, Challenges, and Rewards in Probing Melt Dynamics, Configurational Entropy Change, and Topological Phases of Group V‐ and Group IV‐Based Multicomponent Sulfide Glasses. Issue 11 (10th May 2020) - Chakravarty, Soumendu; Almutairi, Badriah S.; Chbeir, Ralph; Chakraborty, Shibalik; Bauchy, Mathieu; Micoulaut, Matthieu; Boolchand, Punit
Abstract : The observation of reversibility windows (RWs) in binary Ge x S100− x, As x S100− x and ternary Ge x As x S100−2 x glass systems permits constructing a global topological phase diagram in the GeAsS composition triangle. The RW denotes glass compositions for which the enthalpy of relaxation at T g vanishes, leading to thermally reversing glass transitions. The phase diagram permits delineating glass compositions that are in the flexible phase (FP), intermediate phase (IP), and the stressed rigid phase (SRP) for all ternary Ge x As x S100−2 x glass compositions. For the IP compositions examined, a general lowering of the molar volumes, V m, is observed in relation to those for non‐IP compositions, giving rise to a volumetric window. Melt dynamics of IP compositions reveal a fragility index, m  < 20, lower than that for non‐IP melts for which m  > 20 displays a fragility window, underscoring in part the reason for the delayed homogenization of melts in these sulfide glasses. The observations of the three types of window characteristics of IP compositions are feasible only when the homogeneous bulk glasses are synthesized, in which the variance ⟨Δ x ⟩ in As and Ge concentrations, x, across batch compositions is less than 0.01%. This is established by Fourier transform–Raman profiling of each batch of composition that is synthesized. Abstract : The observation of reversibility windows in binary GeS (B, indigo), AsS (A, green), and equimolar ternary GeAsS glasses (A + B + C) permits constructing a global topological phase diagram of the GeAsS ternary glasses for any composition. The colored areas A, B, and C together represent the intermediate phase (IP). The white regions below and above the IP represent the flexible and stressed rigid phases.